Interoperability of multi-agent system in heterogeneous learning management system (HLMS) by deploying wireless sensor networks (WSNS) - Mwinyi, Amir Kombo; Syed Mohamed, Syed Abdul Rahman Al-Haddad; Hashim, Shaiful Jahari; Adnan, Ali Idarous; Abdullah, Rusli (UUM College of Arts and Sciences, Universiti Utara Malaysia, 2013)
User detection in Heterogeneous Learning Management System (HLMS) using sensors which are attached with the Multi-Agent System (MAS) is a new area of research. The integration of sensors with the Multi-Agent system improved the efficiency of LMS by reducing the work load on the LMS servers to the dedicated sensors which are deployed in the domains. In order to explore the potential of sensors and agents, the authors of these papers have integrated these two components so that the efficiency and security of learning management system are realized. In this paper we have introduced the sensors in the web learning system so that the administrators can be aware of the presence of each and every user once connected to the system. The interoperability of Multi-Agent Systems in this learning system is facilitating the retrieval of information from the sensors and sends them to the HLMS servers (Sinks). Furthermore, the information which are gathered and manipulated by the MAS is including measured signal strength of the learning devices and user profile. This information will enable the administrators to know the location of the user in the learning domain and also to notify students on their learning status, based on their profiles which are stored in the database. Hence, a new system model of Multi-Agent System (MAS) with sensor network, in Heterogeneous Learning Management System is presented for improving overall system performance.